2021
DOI: 10.1038/s41467-021-23691-y
|View full text |Cite
|
Sign up to set email alerts
|

Proline/arginine dipeptide repeat polymers derail protein folding in amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis and frontotemporal dementia are two neurodegenerative diseases with overlapping clinical features and the pathological hallmark of cytoplasmic deposits of misfolded proteins. The most frequent cause of familial forms of these diseases is a hexanucleotide repeat expansion in the non-coding region of the C9ORF72 gene that is translated into dipeptide repeat polymers. Here we show that proline/arginine repeat polymers derail protein folding by sequestering molecular chaperones. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 48 publications
3
17
0
Order By: Relevance
“…PR dipeptide repeat proteins are abnormally expressed in the brain of patients with C9-ALS/FTD . The toxicity of PR dipeptide repeat proteins in C9-ALS/FTD is linked to their incorporation into membrane-less compartments, thus changing their properties. , Previous studies demonstrated that the dipeptide repeat protein PR20 interacts with PPIA in vitro and in cells. , …”
Section: Introductionsupporting
confidence: 93%
See 2 more Smart Citations
“…PR dipeptide repeat proteins are abnormally expressed in the brain of patients with C9-ALS/FTD . The toxicity of PR dipeptide repeat proteins in C9-ALS/FTD is linked to their incorporation into membrane-less compartments, thus changing their properties. , Previous studies demonstrated that the dipeptide repeat protein PR20 interacts with PPIA in vitro and in cells. , …”
Section: Introductionsupporting
confidence: 93%
“…To gain single-residue resolution insight into the interaction of PPIA with the dipeptide repeat protein PR20, we used NMR spectroscopy. In agreement with previous results, PR20 induced strong signal broadening of selected PPIA residues. The cross peak of Arg55, the PPIA residue that is crucial for its catalytic activity, was broadened beyond detection (Figure S1a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coordinates of CD147 were derived from the cryo-EM structure (PDB: 6LZ0 23 ), which was determined at 3.30 Å resolution. CypA was performed using its crystal structure (PDB: 7ABT 33 ). CD147-CypA complexes were obtained using the general used Zdock and Rdock programs, 34,35 with the contact residue constraint from the NMR analysis.…”
Section: Protein Structure Preparation and Proteinprotein Dockingmentioning
confidence: 99%
“…A hexanucleotide (GGGGCC) repeat expansion in the first intron of the C9ORF72 gene is a well-established cause for ALS (Braems et al 2020 ). The mutation results in the expression of glycine-arginine and proline-arginine dipeptide repeat proteins, which tend to bind to a large number of intracellular proteins, thereby promoting aggregate formation and consequently DNA damage (Babu et al 2021 ). A study aiming to better understand the mechanism of dipeptide repeat protein-mediated DNA damage using a CRISPR/iPSC-based C9ORF72 disease model revealed that dipeptide repeat proteins such as proline-arginine repeat proteins compromise the proper functioning DNA double-strand repair pathways by inhibiting the action of key proteins such as nucleophosmin (Andrade et al 2020 ).…”
Section: Neurodegenerative Diseases: the Big Picturementioning
confidence: 99%